Pelaksanaan Kemampuan Matematika Awal Melalui Pemanfaatan Media Konkrit Pada Anak Kelompok B Di Tk Xaverius Kalianda - Bandarum , Veronika Iis; Qomario, Qomario; Sulistianah, Sulistianah (JURNAL ILMU PENDIDIKAN, 2023)
This research is motivated by the existence of conditions related to the early mathematical ability is still low. Therefore it is necessary an effort to improve the mathematical ability of children in group B in TK Xaverius Kalianda. This study aims to know that the use of concrete media in learning can improve early mathematical ability in children group B in TK Xaverius Kalianda. This study is a classroom action research consisting of four stages namely, planning, action implementation, observation and reflection. At the beginning of observation of early group math ability in TK Xaverius Kalianda still not developed, as indicator of low early child mathematics ability in kindergarten, this can be seen from 15 children of group B which have progressed development especially in the case of early mathematics only 3 children or 20%, and the rest as many as 12 children or 80% have not been able to develop properly. After the reflection through the use of concrete media there is an increase. The results of this study indicate that through the utilization of concrete media can improve the early mathematical ability of the previously not developed at the time of pre-survey to start developing in the first cycle reached 72% and developed as expected in the second cycle reached 82%. Thus the method of utilizing concrete media can be one of the methods or ways that can be used in learning, especially in improving early math skills.